2019
DOI: 10.9770/jesi.2019.7.2(28)
|View full text |Cite
|
Sign up to set email alerts
|

Targets determination model for VAT risks mitigation at B2B marketplaces

Abstract: The objective of the study is to assess practical requirements for VAT implementation in relation to B2B e-commerce participants for the development and practical implementation of target determination model, considering the mitigation of tax risks associated with transactions on digital marketplaces, taking into account data disclosure upon corporate reporting submission. It was determined in the course of scientific and practical study of the specifics of implementation and payment of indirect taxes, that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…On the one hand, a flat taxation scale, which was supposed to change by 2011, does not encourage economic growth. A progressive scale could stimulate demand from the social layers with a low income, while national demand from the high-income people is unlikely to change because they prefer foreign-made products [1]. One the other hand, we have to take into account correlation of the number of tax payers with different incomes, special regional features.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, a flat taxation scale, which was supposed to change by 2011, does not encourage economic growth. A progressive scale could stimulate demand from the social layers with a low income, while national demand from the high-income people is unlikely to change because they prefer foreign-made products [1]. One the other hand, we have to take into account correlation of the number of tax payers with different incomes, special regional features.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have shown that small enterprises, by providing social stability, provide jobs, and generate public interest in economic stability and resource conservation. (Akhmadeev, 2019). Many researchers have confirmed the importance and necessity of government intervention and assistance to small businesses, which contributes to their unquestionable growth (Orzechowski, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some hormones the human body can synthesize only from special precursors found in food. These precursors are vitamins found in foods Almeida et al, 2019;Prodanova et al, 2019;Melnikov, 2019;Aleksandrova et al, 2019;Filatova et al, 2019;Akhmadeev et al, 2019;Dunets et al, 2019).…”
Section: Basic Power Featuresmentioning
confidence: 99%